Zoom Cloud Meeting: Improving Elementary School Elementary School Students’ Activity and Learning Outcomes: ZOOM CLOUD MEETING: IMPROVING ELEMENTARY SCHOOL ELEMENTARY SCHOOL STUDENTS’ ACTIVITY AND LEARNING OUTCOMES - Hikmiah, Alien Nisaul; Nugroho, Arya Setya (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2024)
This study was conducted to address the challenges of face-to-face meetings, which were found to often clash with elementary school students. Meanwhile, the use of technology by elementary school students is less effective even though they have tools that support internet learning. Therefore, based on these problems, the implementation of learning using Zoom application is expected to solve the problem of physical meeting. This study used Classroom Action Research (CAR) with the stages of planning, implementing, observing, and reflecting in each cycle. Furthermore, data were collected through observation and tests, using instruments in the form of elementary school students’ activity sheets and learning outcomes. The results showed the use of zoom cloud meetings improved elementary school students’ activity and learning outcomes. The activity value was 49.17 in cycle 1 and 68.3 in 2, which fulfills the success indicators of at least 65%. Also, the learning outcomes increased by 23.3% from 56.7% in cycle 1 and 80% in 2. Therefore, the Zoom application can be used for online learning, which is proven to increase the number of elementary school student attendance and their learning outcomes.